FORMALIZATION OF THE CULTURAL HERITAGE MANAGEMENT MODEL AS A FACTOR OF TOURISM DEVELOPMENT IN THE RUSSIAN FEDERATION - Ernest E. Ibragimov; Ibraim E. Avdil’ (Russian Studies in Culture and Society)
The article formalizes the model of cultural heritage management, clarifies the content of cultural heritage cognition by considering the processes of studying, preserving and using cultural heritage objects as a factor in the development of tourism in the Russian Federation, taking into account modern challenges and opportunities.